Development of an Interactive E-book to Improve Student's Problem Solving - Lieung, Karlina Wong; Rahayu, Dewi Puji; Yampap, Umar (Jurnal Ilmiah Sekolah Dasar, 2021)
Lack of digital-based learning resources makes students experience problems in learning. This is because conventional learning resources are less practical so students prefer innovative learning sources. This study aims to compile and use innovative and creative teaching materials by the curriculum, student development, and information technology developments. This research is classified as a development research type with the Dick and Carey model. The research data were analyzed descriptively quantitatively. The results of the E-book development show that it is very feasible to use. The score obtained is 3.8 or 95% from the validator. This e-book is also considered practical with an average value of 84.07%. The practical value is known by conducting individual trials, large group trials, and teacher assessments. The results of the field test showed that the interactive e-book developed was able to improve problem-solving skills in grade IV students. After being given an interactive e-book, the students' scores classically increased to 92.59%. Based on the results of the study, it can be concluded that the interactive e-book developed meets the standards of feasibility, practicality, and effectiveness for use in grade IV SD students. The implication of this research has the impact of increasing student motivation in learning so that it affects student learning outcomes that increase.